Oxygen isotope systematics of chondrules in the Paris CM2 chondrite: indication for a single large formation region across snow line - Chaumard, Noël; Defouilloy, Céline; Hertwig, Andreas; Kita, Noriko T. (Geochimica et cosmochimica acta, 2021)
In-situ oxygen three-isotope analyses of chondrules and isolated olivine grains in the Paris (CM) chondrite were conducted by secondary ion mass spectrometry (SIMS). Multiple analyses of olivine and/or pyroxene in each chondrule show indistinguishable Δ17O values, except for minor occurrences of relict olivine grains (and one low-Ca pyroxene). A mean Δ17O value of these homogeneous multiple analyses was obtained for each chondrule, which represent oxygen isotope ratios of the chondrule melt. The Δ17O values of individual chondrules range from −7‰ to −2‰ and generally increase with decreasing Mg# of olivine and pyroxene in individual chondrules. Most type I (FeO-poor) chondrules have high Mg# (∼99) and variable Δ17O values from −7.0‰ to −3.3‰. Other type I chondrules (Mg# ≤97), type II (FeO-rich) chondrules, and two isolated FeO-rich olivine grains have host Δ17O values from −3‰ to −2‰. Eight chondrules contain relict grains that are either 16O-rich or 16O-poor relative to their host chondrule and show a wide range of Δ17O values from −13‰ to 0‰. The results from chondrules in the Paris meteorite are similar to those in Murchison (CM). Collectively, the Δ17O values of chondrules in CM chondrites continuously increase from −7‰ to −2‰ with decreasing Mg# from 99 to 37. The majority of type I chondrules (Mg# >98) show Δ17O values from −6‰ to −4‰, while the majority of type II chondrules (Mg# 60-70) show Δ17O values of −2.5‰. The covariation of Δ17O versus Mg# observed among chondrules in CM chondrites may suggest that most chondrules in carbonaceous chondrites formed in a single large region across the snow line where the contribution of 16O-poor ice to chondrule precursors and dust enrichment factors varied significantly.